Public Service, Leadership and Innovation in South Africa - Msila, Vuyisile (Technium Social Sciences Journal, 2022)
In South Africa public service institutions are the implementing arm of government. These include services such as education, electricity, health, housing, transport and water. Government services such as municipalities are also part of this and have always bore the brunt of citizens who protest about the non-delivery of services. Community members demanding service delivery from government departments have been initiating unending strikes which are frequently destructive. Yet, various South African government departments have experienced employees’ non-commitment, corruption and wastage of government resources. The purpose of this article is to utilize literature review to examine the role of public service leaders in transforming public service for effective governance. Arguably, public service institutions with weak leadership and no vision will always falter. The discussion focuses on how conscientious leaders can employ values, ethics and ownership to strengthen the function of these public service institutions. Furthermore, the article examines how in a time of decolonization and transformation leaders could adapt strategies for revamped African public institutions. The conclusions show that it would not be enough for leaders to know the Batho Pele principles and the Constitution of the democratic South Africa of 1996, but it is being able to be a transformational and ethical leader that one can lead public service institutions.